2023
DOI: 10.1021/acsbiomaterials.3c00061
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Lung Surfactants Attenuate Direct Lung Injury in Mice

Abstract: If not properly managed, acute lung injuries, either through direct or indirect causes, have the potential to present serious risk for many patients worldwide. One of the mechanisms for the transition from acute lung injury (ALI) to the more serious acute respiratory distress syndrome (ARDS) is the deactivation of the native lung surfactant by injury-induced infiltrates to the alveolar space. Currently, there are no surfactant replacement therapies that are used to treat ALI and subsequent ARDS. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We further investigated whether FCVJ can be used to determine the T g of nanoconfined polymers. Specifically, we were interested in measuring polymer micelle core T g in aqueous solution because T g is an important factor contributing to the performance of polymer micelles, for instance, in lung surfactant therapy and controlled drug release applications. FCVJ was loaded within the hydrophobic PS core domain of spherical micelles (having a core diameter of 20 nm) formed in water by PS 54 –PEG 114 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated whether FCVJ can be used to determine the T g of nanoconfined polymers. Specifically, we were interested in measuring polymer micelle core T g in aqueous solution because T g is an important factor contributing to the performance of polymer micelles, for instance, in lung surfactant therapy and controlled drug release applications. FCVJ was loaded within the hydrophobic PS core domain of spherical micelles (having a core diameter of 20 nm) formed in water by PS 54 –PEG 114 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a saturated lipid, dipalmitoyl­phosphatidyl­choline (DPPC), is enriched to up to 40% of the total lipid content in the alveoli in order to be able to reduce the surface tension of the alveolar lipid monolayer down close to zero at end expiration. , Similarly, Langmuir monolayers of synthetic homopolymers and block copolymers , have been shown to exhibit a wide range of surface mechanical behavior depending on the relaxation dynamics of the polymer molecules. However, using synthetic polymers to control the surface mechanical properties of physiological air–water interfaces for therapeutic purposes is challenging because it is difficult to molecularly spread polymers on the water surface without using an organic spreading solvent. , Recently, our group has demonstrated that water-spread monolayers of amphiphilic block copolymer micelles can have surface mechanical characteristics that closely mimic those of natural lung surfactant monolayers; aqueous micelles formed with poly­(styrene- block -ethylene glycol) (PS-PEG) block copolymers spontaneously spread on the water surface (without undergoing any change in micellar morphology) and form an insoluble micelle monolayer that is capable of producing near-zero surface tension under high compression. , This micelle monolayer system bears a resemblance to polymer-brushed nanoparticle monolayers and differs from the conventionally studied block copolymer films. The latter are typically prepared by spreading the polymer from a state of singly dispersed chains using cosolvents, forming a continuous asymmetric monolayer or “surface micelles”. , For clinical and therapeutic applications, it is imperative that polymers are administered in an aqueous suspension, precluding the use of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Serum proteins are known to competitively adsorb at the air–water interface within alveoli, functioning as inhibitors for lipid-based lung surfactants, whether natural or synthetic, during lung injury situations (as depicted in Figure ). , Our previous research has demonstrated that PLS maintains its capability to lower surface tension (increase surface pressure (Π)), even in the presence of albumin, a model serum protein. , Moreover, PLS naturally remains unaffected by enzymatic degradation by phospholipases, which are activated under inflammation . Given its commendable physiological behavior and economical feasibility for production scale-up, PLS holds substantial promise as an alternative to current lipid-based lung surfactants for treating conditions such as ARDS and related ailments …”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently demonstrated in-depth evidence of the efficacy of using aqueous amphiphilic block copolymer (BCP) micelle solutions as respiratory therapeutics which function by temporarily replacing the native lung surfactant, a substance which reduces the high air–water surface tension ( γ ) within alveoli, following lung injury. 1,2 The technology, referred to as polymer lung surfactant (PLS), has promising potential to serve as an effective therapeutic for a very deadly condition known as Acute Respiratory Distress Syndrome (ARDS). One of the contributing factors for the high (∼40%) 3 mortality rate for ARDS patients is the dysfunction of native lung surfactant which is a crucial component of the proper respiratory function.…”
Section: Introductionmentioning
confidence: 99%